Seasonal survey, risk factor's analysis and genotyping of Theileria annulata infecting cattle in Punjab province, Pakistan - Asif, Muhammad; Ben Said, Mourad; Parveen, Asia; Ejaz, Arusa; Ikram, Muhammad; Awais, Mian Muhammad; Iqbal, Furhan (Elsevier, 2022)
Theileriosis is one of the most frequently reported tick borne diseases in tropical and subtropical regions and leads to annual economic losses, such as the reduced dairy products and increased casualties. Tropical theileriosis is caused by Theileria annulata and the present study was designed to improve our knowledge of Theileria annulata infection in Pakistani cattle. In order to assess the prevalence of Theileria annulata on cattle from Multan district in the Punjab province (Pakistan) according to seasons and other risk factors, a total of 1020 blood samples (340 samples each from cross, Holstein Frisian and Sahiwal breed) were collected between 2020 and 2022. Based on Tams-1 partial sequence amplification, the overall T. annulata prevalence was estimated at 11.3% (115/1020). The highest prevalence was observed in autumn season (14.1%), followed by winter (12.9%), summer (11.4%) and spring (6.7%) season. Sahiwal cattle were most susceptible to T. annulata infection (13.2%) followed by Crossbred (11.8%) and Holstein Frisian (8.8%). Epidemiological factor analysis revealed that female cattle, cattle rose with other dairy animals at farm, tick infested cattle, and cattle raised with dogs infested with ticks were associated with the prevalence of T. annulata. White blood cells, lymphocyte (%), Monocyte (%) hemoglobin, mean cell hemoglobin, mean corpuscular hemoglobin concentration, and platelet count were significantly affected blood parameters in T. annulata positive cattle of all three breeds. Representative partial Tams-1 se-quences of four Pakistani T. annulata isolates revealed a single genotype genetically close to those infecting cattle from neighboring countries like Iran, Turkey and Egypt. Longitudinal survey and phylogenetic positioning of T. annulata is recommended for epidemiological correlation, diagnosis and treatment of theileriosis in such an agricultural region of Pakistan.
Keywords: Theileriaannulata; Molecularprevalence; Riskfactors; Phylogeneticanalysis; Cattlebreeds